PENANGGUNGJAWAB PENDIDIKAN - Qamar, Syamsul (Idaarah: Jurnal Manajemen Pendidikan, 2017)
Education is a conscious and planned effort to create an atmosphere of learning and learning process so that learners actively develop their potential to have religious spiritual power, self-control, personality, intelligence, noble character and skills needed for him, nation society and country.The ideas mentioned above will only be implemented if education is really well implemented by those mandated to pursue such education, among others; parents, educators, community and government.With respect to education responsibilities, parents should be responsible for the implementation of education in the household, educators responsible for the ongoing education in schools/universities and the government is responsible for the implementation of the national education process.